PENGARUH PENERAPAN KERAJINAN CIRI KHAS DAERAH TERHADAP KREATIVITAS SISWA PADA MATA PELAJARAN SBDP KELAS IV DI SD NEGERI 39 PRABUMULIH - Hartini, Ria; Al Ihwanah; Tasya Jadidah, Ines (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing regional characteristic handicrafts on students’ creativity in Arts, Culture, and Crafts (SBdP) learning for fourth-grade students at SD Negeri 39 Prabumulih. This research is motivated by the condition that students’ creativity in SBdP learning has not developed optimally due to the lack of utilization of learning activities based on local wisdom, resulting in students’ creative potential not being maximally explored. This study employed a quantitative approach with a quasi-experimental research design using a pretest–posttest non-equivalent control group design. The research subjects consisted of 66 students divided into two groups: an experimental class of 34 students who received learning through the implementation of regional characteristic handicrafts and a control class of 32 students who did not receive the treatment. The independent variable in this study was the implementation of regional characteristic handicrafts, while the dependent variable was students’ creativity.Data collection techniques included observation, documentation, and questionnaires (students’ creativity tests). The data were analyzed through prerequisite testing in the form of a normality test. Since one of the data sets was not normally distributed, hypothesis testing was continued using the nonparametric Mann–Whitney U Test. The results of the analysis showed an Asymp. Sig. (2-tailed) value of 0.000, which is smaller than α = 0.05. These results indicate that the implementation of regional characteristic handicrafts has a significant effect on students’ creativity. Therefore, the implementation of regional characteristic handicrafts can be used as an effective alternative learning approach to improve students’ creativity in SBdP learning at the elementary school level.